Kombinasi Metode Kontrol dan Perkuatan untuk Penanganan Longsor (Studi Kasus: Longsor Waikerap, Tanggamus, Lampung) - Aminudin Syah; Ilham Dani; Sandri Erfani (Borneo Engineering : Jurnal Teknik Sipil, 2020)
Landslides often cause heavy casualties and material losses in Tanggamus Regency. These incidentscontinue to be repeated so that it still requires a landslides risk reduction. Landslides risk mitigation begins with a field survey and soil investigation, followed by analyzing the investigation results and planning the potential mass movements. The results from the geological survey show that the study area has a lithology of constituents in the form of andesite and landslide material in the form of volcanic breaks with a high level of weathering so as to form a thick layer of soil. The basic landslide handling design plan in Pekon Waykerap is to perform the geometry arrangement of the slopes so itprovides a strengthened structure with gabion slopes. The slope design results give the slope height limited to 5 meters, a 1H:1V slope gradient, and 2.5 meter bench. The slope surface is suggested to be covered with a patch of grass and equipped with surface drainage. The slope stability analysis results for Pekon Waykerap landslides using the limit equilibrium method shows that using the combination of control and retrofitting method and increases the static safety factor from 1.092 to 1.298 and the dynamic safety factor from 0.846 to 1.031, which means the groundmass movement risk decreases.